Comparative cytogenetics of eight species of Cycloramphus (Anura, Cycloramphidae) - Noleto, Rafael Bueno; Amaro, Renata Cecilia; Verdade, Vanessa Kruth; Cruz Campos, Joao Reinaldo [UNESP]; Kraft Gallego, Luiz Fernando; Xavier de Lima, Andre Magnani; Cestari, Marta Margarete; Kasahara, Sanae [UNESP]; Yonenaga-Yassuda, Yatiyo; Rodrigues, Miguel Trefaut; Toledo, Luis Felipe (Elsevier Gmbh, Urban & Fischer Verlag, 2011)
Several aspects of the biology of Cycloramphus species of the Atlantic Forest are still poorly known, which makes it difficult to understand their historical relationships. Therefore, we were stimulated to promote a comparative cytogenetic analysis of several species of the genus Cycloramphus. The study of Cycloramphus acangatan, C. boraceiensis, C. brasiliensis, C. carvalhoi, C. eleutherodactylus, C. fuliginosus, C. lutzorum, and C. rhyakonastes, revealed that these eight species share a diploid number 2n=26. Cycloramphus fuliginosus presented the most distinct karyotype, due to the presence of subtelocentric chromosomes in pairs 1 and 4. The main diagnostic feature observed in the other species was the presence of one pair of telocentric chromosomes in C. boraceiensis, C. carvalhoi, and C. eleutherodactylus, while the remaining species presented karyotypes composed exclusively of biarmed chromosomes. Constitutive heterochromatin was predominantly located in pericentromeric regions in all species, although additional C-bands detected on telomeric and/or interstitial regions were partially species-specific. Silver staining revealed Ag-NORs located on the pair 6 in six species, whereas C. acangatan presented it on pair 1 and a multiple pattern was observed in C. fuliginosus with three Ag-NOR bearing chromosomes. Fluorescent in situ hybridization using rDNA probe was performed in specimens of C. eleutherodactylus from Parana, C. lutzorum, and C. rhyakonastes, which did not reveal inactive NOR. Despite the apparent highly conserved diploid number, data on the karyotype microstructure characterize the cytogenetic profile of the genus and may contribute to clarify the phylogenetic relationships among Cycloramphus, the Cycloramphinae, or even the family Cycloramphidae. (C) 2011 Elsevier GmbH. All rights reserved.
Keywords: Amphibian cytogenetics; Cycloramphus; Karyotypes; Ag-NORs; C-banding; FISH